1999
DOI: 10.1101/gad.13.5.511
|View full text |Cite
|
Sign up to set email alerts
|

Gene targeting in the silkworm by use of a baculovirus

Abstract: The Bombyx mori fibroin light (L)-chain gene was cloned and the green fluorescent protein (GFP) gene inserted into exon 7. The chimeric L-chain-GFP gene was used to replace the polyhedrin gene of Autographa californica nucleopolyhedrovirus (AcNPV). This recombinant virus was used to target the L-chain-GFP gene to the L-chain region of the silkworm genome. Female moths were infected with the recombinant virus and then mated with normal male moths. Genomic DNA from their progenies was screened for the desired ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(48 citation statements)
references
References 19 publications
1
46
0
1
Order By: Relevance
“…Several methods have been established for generating transgenic silkworms (Bombyx mori) (8)(9)(10)(11). Accordingly, transgenic silkworms have been studied as tools for large-scale production of foreign recombinant proteins because silkworm silk glands have a high capacity for protein biosynthesis (12)(13)(14).…”
mentioning
confidence: 99%
“…Several methods have been established for generating transgenic silkworms (Bombyx mori) (8)(9)(10)(11). Accordingly, transgenic silkworms have been studied as tools for large-scale production of foreign recombinant proteins because silkworm silk glands have a high capacity for protein biosynthesis (12)(13)(14).…”
mentioning
confidence: 99%
“…Spontaneous mutations found while practicing sericulture were used to help establish principles of classical genetics, including sex linkage and the discovery of no crossing over in lepidopteran females (Tanaka 1913;Sturtevant 1915), maternal mutations (Toyama 1912), homeotic mutants and complex loci (Ichikawa 1943;Tsujita 1953), and the construction of early linkage maps (Fujii et al 1998;Yasukochi et al 2005). With the establishment of stable transformation (Yamao et al 1999;Tamura et al 2000), the silkworm has shown the potential to produce pharmaceutically important proteins in high yield (Tomita et al 2003), opening up new applications for sericulture in medical, agricultural, and industrial fields.…”
mentioning
confidence: 99%
“…It has been reported previously that the proliferation of B. mori AcNPV is related to the virus concentration (Shikata et al, 1998;Yamao et al, 1999). To investigate this, we compared the proliferation of B. mori AcNPV in both HPS and LPS, both in terms of the duration since injection, and the initial concentration of virus used.…”
Section: Discussionmentioning
confidence: 99%
“…So, the baculovirus expression system, AcNPV, is commonly applied for large scale expression for eukaryotic proteins in permissive cell lines or insects (Maeda, 1989). In AcNPV hosted by A. californica has been used to infect cultured cells derived from B. mori, but they can fail to breed (Shikata et al, 1998;Yamao et al, 1999). Recently however, the existence of a B. mori strain that enabled the breeding of AcNPV has been reported Lee et al, 2007).…”
Section: Introductionmentioning
confidence: 99%